2001
DOI: 10.1143/jjap.40.4162
|View full text |Cite
|
Sign up to set email alerts
|

Protonic Conduction in the Single Crystals of SrZr0.95M0.05O3 (M=Y, Sc, Yb, Er)

Abstract: The relativistic framework with its symmetries offers a natural definition for the internal time of classical (non-quantum) physical systems as a Lorentz-invariant observable. The internal-time observable, measuring the system's aging or internal evolution, is identified with the proper time of the system derived from its centre-of-mass (CM) coordinate. For its definition as an observable it is required that the system be symmetric not only under Lorentz-Poincaré transformations but also under uniform scaling,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
32
0
2

Year Published

2004
2004
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 10 publications
5
32
0
2
Order By: Relevance
“…The s N of p-SZY5 and its activation energy (0.59 eV) determined in this study agree well with those of the s-SZY5 (See Fig. 2) [28,30]. The slope of s N changes in the temperature region above w450 C due to the loss of protons, consistent with previous observations [28,30].…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…The s N of p-SZY5 and its activation energy (0.59 eV) determined in this study agree well with those of the s-SZY5 (See Fig. 2) [28,30]. The slope of s N changes in the temperature region above w450 C due to the loss of protons, consistent with previous observations [28,30].…”
Section: Resultssupporting
confidence: 90%
“…3 displays the Arrhenius plots of the bulk and specific grain-boundary conductivities of the p-SZY5 (s N and s gb , respectively, and the subscripts N and gb denote bulk and grain boundary hereafter). Also included for comparison are the plots of single crystal SZY5 (s-SZY5) previously reported [28,30]. It should be noted that the specific grain-boundary conductivity is defined to be average conductivity of a grain boundary.…”
Section: Electrical Measurementmentioning
confidence: 99%
“…• C, the conductivity in the humidified atmosphere was larger than that in both dry atmospheres, in agreement with other studies on protonconducting crystals 40,41 . The significant increase in the activation energy under dry conditions, compared with wet conditions, clearly indicated that the nature of the charge carriers changed 42 .…”
Section: R Educing the Sofc Operating Temperature In The Intermediatesupporting
confidence: 92%
“…Higher order coupling terms may exist between the optical mode and strain when considering the Imma to I4/mcm transition. Probably due to coupling between the soft optic mode and spontaneous strain, the softening is incomplete in the phonon modes of SrZrO 3 . In both our previous 13) and present papers we have demonstrated three phase transitions of SrZrO 3 from the point of view of lattice dynamics.…”
Section: Discussionmentioning
confidence: 99%